North Atlantic Oscillation polarity during the past 3 ka derived from lacustrine sediments of large lowland lake Schweriner See, NE-Germany - Adolph, Marie-Luise; Czerwinski, Sambor; Dreßler, Mirko; Strobel, Paul; Bliedtner, Marcel; Lorenz, Sebastian; Debret, Maxime; Haberzettl, Torsten (2023)
Based on a multi-dating and multi-proxy approach, we reconstruct Late Holocene environmental changes from sediments of Schweriner See, a large lowland lake in NE-Germany spanning the past 3070 +170 / -210 cal BP. We infer large-scale atmospheric variations using a combination of in-lake productivity indicators using traditional and high-resolution techniques (e.g. LOI 550 , TOC, inc/coh), diatom assemblages, which are sensitive to ice-cover duration, as well as compound-specific hydrogen isotopes (δ 2 H C25 ) reflecting variability in the moisture source region distinguishing the southern and northern North Atlantic and/or Arctic region and/or the degree of evaporative lake water enrichment. Our study shows that before 1850 CE, in-lake productivity at Schweriner See was mainly influenced by winter temperature variability, which modulates ice-cover duration and growing-season length. Low productivity co-occurs with the occurrence of the diatom species Stephanocostis chantaicus , which blooms below the ice cover, indicating temporal prolonged ice cover duration. Simultaneously, changes to a moisture source region in the northern North Atlantic and/or Arctic regions and/or low evaporative lake water enrichment are inferred from δ 2 H C25 . In contrast, high productivity is linked to the disappearance of S. chantaicus and moisture originating from the southern North Atlantic and/or high evaporative lake water enrichment. These distinct changes are driven by variations between positive and negative NAO polarity during the past 3070 +170 / -210 cal BP. Besides these long-term shifts in atmospheric conditions, short-term variations can be inferred from titanium concentrations, which mainly reflect paleo-shoreline distance likely linked to precipitation variability and, after the 12 th century, to anthropogenic impacts. Since 1850 CE, productivity has been driven by nutrient availability.